The current situation of health equity in underserved areas of Afghanistan - Salem, Marwa Rashad; Hegazy, Nelly; Eldeeb, Sherif; Shaguy, Jerome A.; Nassery, Ramesh Mohammad; Khawari, Abdullah; Tanoli, Jamshed; Abouzeid, Alaa (Frontiers in Public Health, 2024)
Background: In the Afghanistan context, providing universal health coverage (UHC) in the spirit of the UHC declaration is challenging on two fronts: the geographic topography of the country and the gender dynamics in the local culture.We Conducted a desk review on underserved areas in the context of health services by gathering and analyzing existing literature, reports, and data using a combination of keywords and phrases these being: "underserved areas," "healthcare disparities," "access to healthcare," "health services,". The central data source is the underserved population analysis undertaken by WHO Afghanistan's emergency program and data from in-country partners. In addition to other reports, this review focused on the analysis of the geographical availability of PHC services using the SPHERE's framework prescriptions and the social realities within the Afghan population that may erect barriers to equity in terms of demand and access to PHC services.Although there are a significant number of primary health care facilities in operation (4242), they are unevenly distributed across different regions of Afghanistan, resulting in almost 25% of the population being underserved. The underserved population is nearly equally distributed between sexes, and the majority live in rural communities. Females in the childbearing period represent 28% of the underserved population. Under-5 Children are 16% to 18% of the underserved population in all regions, except in the Western region, where they are between 12% and 13%. While those over 60 years old are from 1% to 3% across all regions. More than 50% of the population of the Central Highland region of Afghanistan is underserved, followed by the Western Region and the Southern Region. Ghor province in the Western region shows the highest proportion of underserved populations, followed by Zabul province in the Southern region.Afghanistan is currently experiencing a protracted humanitarian crisis, with millions of people living in poverty or without access to health care, placing them at serious risk of disease epidemics, starvation and maternal and child mortality. It becomes fundamental to take alternative strategies to reach the highly affected populations and to increase funding for the delivery of healthcare services in Afghanistan.